Differences between experts and confirmed weightlifters during the preparation phase - Bolliet, O.; Collet, C.; Dittmar, A. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction Two main sequences could be observed during the Olympic snatch movement preparation. First, the competitor is called on stage and goes automatically through the usual steps. Then, he remains standing in front of the bar. As a rule, from what they could say, they attempt to prepare the movement by a mental control of a technical aspect, probably that they do not master properly. The second stage begins as far as the weightlifter has placed his hands on the bar. Mental activities such as focusing attention on a technical aspect of movement and increasing general activation has been evidenced in weightlifting preparation period (Bolliet, Collet & Dittmar, 2002). The aim of this study was to differentiate elite from confirmed weightlifters preparation. Subjects, material and method Subjects were divided into two groups according to their performance level. Five elite and 7 confirmed weightlifters were asked to perform the first Olympic movement: the snatch. The load could carry from 90 to 95%. Six autonomic variables (2 electrodermal, 2 thermovascular and 2 cardiorespiratory) were continuously recorded during the experiment. Multiparametric recordings through sensitive micro-sensors and new indices of autonomic nervous system (ANS) activity quantification have brought new concepts on ANS physiological functioning (Dittmar et al., 1997). Recent findings related to ANS functions have led to consider vegetative activity as reflecting some brain functions in real time (Hugdahl, 1996). Simultaneous and continuous measurements of ANS activity during motor performance might lead to a better understanding of such mental processes. Phasic responses (sudden variations) are related to focused attention and tonic activity (slow variations) to general activation. Results In the elite population, 154 phasic responses were observed during the first phase vs 44 during the second phase (154/44, i.e. ratio 3.5). In the confirmed population 164 phasic responses were observed during the first phase vs 79 during the second phase (164/79, i.e. ratio 2.1); U=25, P>.05. Subject-bysubject analysis (phasic responses ratio between phase 1 and 2) showed that 4 confirmed subjects behavior were close to elite subjects behavior.